Kindlin‐3 negatively regulates the release of neutrophil extracellular traps. Issue 3 (14th April 2018) - Xu, Zhen; Ni, Beiwen; Cao, Zhongyuan; Zielonka, Jacek; Gao, Juan; Chen, Fangyuan; Kalyanaraman, Balaraman; White, Gilbert C.; Ma, Yan‐Qing
Abstract: Neutrophils fight infections by generating reactive oxygen species (ROS) and extracellular traps (NETs). However, how neutrophils modulate ROS/NET generation is mechanistically unclear. Kindlin‐3, an essential integrin activator expressed in hematopoietic cells, is required to support integrin‐mediated neutrophil recruitment during inflammation. Here, we report a novel role of kindlin‐3 in regulating ROS/NET generation in neutrophils. When overexpressing kindlin‐3 in neutrophil‐like differentiated HL‐60 cells (HL‐60N), ROS/NET generation from these cells were significantly suppressed. Interestingly, overexpression of a kindlin‐3 mutant that is defective for interacting with integrins in HL‐60N cells still inhibited ROS/NET generation, suggesting that the role of kindlin‐3 in inhibiting ROS/NET signaling may be independent of its binding to integrins. Consistently, knockdown of kindlin‐3 in HL‐60N cells led to enhanced ROS/NET generation. In addition, bone marrow neutrophils isolated from kindlin‐3‐deficient mice showed elevated ROS/NET generation when compared with WT counterparts. As expected, overexpression of exogenous kindlin‐3 in mouse neutrophils could suppress NET release ex vivo and in vivo . Collectively, these results demonstrate that kindlin‐3 in neutrophils is involved in modulating the ROS/NET signaling, providing a novel mechanism for fine‐tuning neutrophil behaviors during inflammation. Abstract : Kindlin‐3 is a novel regulator for fine‐tuning the generation of ROS/NETs in neutrophils during inflammation.